High-resolution patterning of silica nanoparticle-based ionogels by reverse-offset printing and its characterization. (1st September 2022) - Kusaka, Yasuyuki; Kimnannara, Khiev; Koutake, Masayoshi; Kano, Shinya; Furukawa, Hiromitsu; Fukuda, Nobuko
Abstract: In this study, nanoparticle-based, high-resolution patternable ionogels are presented to provide a route for realizing printed solid-state ionic devices. By incorporating an ionic liquid (IL) into a spherical silica nanoparticle suspension, a quasi-solid ionogel layer compatible with reverse-offset printing (ROP) with a spatial resolution of approximately 5 μ m was realized. In situ near-infrared (NIR) spectroscopic analysis revealed the drying kinetics of the ionogel ink during printing, and a temporal margin for successful patterning in relation to its dry state was provided. In contrast to polymer-based gels, the present ionogel can be regarded as a porous medium of silica filled with ionic liquids with a certain degree of saturation. By optimizing the ink formulations, ROP patterning was successful for saturation up to 102%, indicating the nanoscale pores between silica nanoparticles can be fully used as an ion-conductive phase in the proposed patternable gel. The conductivity depends drastically on saturation, with a saturation exponent of approximately −7 according to Archie's law. From a complementary scratch test, an ionogel at a saturated condition still exhibited fragile but solid-like characteristics. As a demonstration, planar micro-supercapacitors fully printed with reverse-offset printable ionogel and carbon inks were fabricated. A comparison with a drop-casted IL showing a similar capacitance indicates a limited ability of the carbon nanoparticle material used here, while a relatively high resistance of the silica-nanoparticle-based ionogel hinders a fast cyclic voltammetry response.